Formation of students’ social competence in the context of additional vocational education - Sokolova, Natalia Leonidovna (2021)
The article is devoted to the urgent problem of the formation of students’ social competence while receiving additional vocational education. The study highlights the specifics of the examination of this phenomenon in modern science and the significance of the development of students’ social competence. The article also emphasizes the fact that the development of the given asset is especially effective within the training activity in addition to the traditional educational environment of a university, in particular, in the context of the various forms of additional vocational education. The research is aimed at studying the specifics of the formation of students’ social competence while receiving additional vocational education. To achieve the goal of the research, an experiment aimed at studying the state and dynamics of students’ social competence was developed and carried out. The research methodology and its algorithm were selected, which include a complex psychological and pedagogical experiment and tracking the state and dynamics of social competence before and after the formative influence. The study was carried out at the Department of Social Pedagogy of the Institute of Foreign Languages of the Peoples’ Friendship University of Russia. The study involved 40 students; the sample was representative in terms of gender and other characteristics. The results of the study allow concluding that training is an effective method for the formation of students’ social competence in the context of additional vocational education. The results of the experiment and their interpretation confirm this hypothesis.